Relationship between physical activity levels of Portuguese physical therapists and mental health during a COVID-19 pandemic: Being active is the key - Almeida, Laura Cristina; Grilo, Ana; Carolino, Elisabete; Tomás, Maria Teresa (Frontiers in Public Health, 2022)
Introduction Physical activity is essential for a healthy life and quality of life, representing a fundamental role in individuals' physical and mental health. Concomitantly, the physical therapist, through the promotion of physical activity and exercise, can improve mental health, an essential factor in the current pandemic, triggering anxiety, fear, and depression crisis. Objective To verify physical activity among Portuguese physical therapists and its association with mental health during pandemic times. Methods An online questionnaire was applied through social media to all Portuguese physical therapists between October 21, 2021, and January 14, 2022. It contained general characterization questions of the sample, the IPAQ-SF questionnaire to assess physical activity levels, the Goldberg General Health Questionnaire (GHQ-28), which assesses the levels of mental health and the WHO Well-Being Index (WHO-5) to assess the subjective wellbeing. Results The sample totaled 286 respondents (82% female), with a mean age of 33. Of the total answers, 82% practiced physical activity, 45% had moderate levels of physical activity, and 19% vigorous. Physical therapists in these categories had lower values in the GHQ-28 and higher in the WHO-5. Those with better mental health also showed better subjective wellbeing (r = −0.571, p = 0.000). Conclusion The data obtained showed that physical therapists mostly have moderate and vigorous levels of physical activity and that physical activity positively influences individuals' mental health and wellbeing, which proved to be a key factor due to the pandemic situation.